Who is the greatest team in Liga MX? A dynamic analysis - Corona, Francisco; Muriel, Nelson; López-Pérez, Jesús (Estudios Económicos de El Colegio de México, 2023)
In this paper, we conduct a statistical procedure to respond a very frequent question in Mexican sport media TV: Who is the greatest team in Liga MX? For this purpose, we apply Principal Components to a historical domestic and international results database along with variables related to the fans and the market value of the franchises’ roster from 2011-2019. The results allow us to analyze the evolution of the “greatness” latent variable over time, concluding that, in the window of time analyzed, Club América is the greatest team, followed by C.D. Guadalajara and C.F. Cruz Azul. Additionally, nowadays, Club Tigres de la Universidad Autónoma de Nuevo León and C.F. Monterrey displace teams like Deportivo Toluca F.C. and Club Universidad Nacional.